2015
DOI: 10.1177/0284185115585035
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of CT appearances in renal oncocytoma and chromophobe renal cell carcinoma

Abstract: CT imaging features such as stellate scar, spoken-wheel-like enhancement, and segmental enhancement inversion were more common in RO and they may help in differentiating RO from ChRCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
2
26
1
1
Order By: Relevance
“…For example, Rosenkrantz [10] stated that MRI features including fat, hemorrhage, margin of the mass, perirenal fat infiltration, renal vein cancer thrombus, enhancement uniformity, vascular proliferation and central scar, and segmental enhancement inversion cannot be used to distinguish between chRCC and RO. Wu et al [9] reported that cases of RO present more instances of central scar, radial enhancement, and segmental enhancement inversion than those observed for chRCC on contrast-enhanced CT. Kim et al [18] asserted that differential diagnosis between different tumor types can be achieved by CT enhancement. Most cases of chRCC showed homogeneous enhancement, whereas most renal clear cell and papillary cell carcinomas showed heterogeneous enhancement.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Rosenkrantz [10] stated that MRI features including fat, hemorrhage, margin of the mass, perirenal fat infiltration, renal vein cancer thrombus, enhancement uniformity, vascular proliferation and central scar, and segmental enhancement inversion cannot be used to distinguish between chRCC and RO. Wu et al [9] reported that cases of RO present more instances of central scar, radial enhancement, and segmental enhancement inversion than those observed for chRCC on contrast-enhanced CT. Kim et al [18] asserted that differential diagnosis between different tumor types can be achieved by CT enhancement. Most cases of chRCC showed homogeneous enhancement, whereas most renal clear cell and papillary cell carcinomas showed heterogeneous enhancement.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, RO is characterized by homogeneous enhancement of the solid mass. The enhancement of RO and chRCC at each stage is lower than that of the normal renal cortex; however, enhancements of RO are more prominent than those of chRCC [9]. Thus, in clinical practice, it is difficult to distinguish chRCC from RO only by visual imaging.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1315161832] Among RCCs, a central stellate scar appeared to be an exclusive feature of the chromophobe subtype although it may also be found in oncocytoma. [192021] All cases involving a central stellate scar on imaging were confirmed histologically.…”
Section: Discussionmentioning
confidence: 98%
“…[18] Spoke-wheel enhancement and a central stellate scar – imaging findings initially observed in oncocytomas have recently been recognized in chromophobe RCCs as well. [192021] Several studies evaluated the degree of RCC enhancement subjectively and quantitatively[13222324252627] while others correlated magnetic resonance imaging (MRI) findings such as diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) values, with the RCC subtype. [28293031] Thus, the objectives of this present study were: (1) to define the characteristic imaging appearances of the various RCC subtypes including quantifying the degree of tumor enhancement, (2) to integrate the imaging findings with relevant demographic and clinical parameters, and (3) to frame the results of this study in the context of the existing literature.…”
Section: Introductionmentioning
confidence: 99%